Petrolisthes tanmayi sp. nov., a new species of the porcelain crab (Decapoda: Anomura: Porcellanidae) from G-Plot Island, Sundarbans, India - Pahari, Priti Ranjan; Das, Shubhrajyoti; Das, Mitali; Maiti, Subhadeep (Zootaxa, 2025)
A new species of porcelain crab Petrolisthes tanmayi sp. nov. is described from G-Plot Island, Sundarbans, West Bengal, India. The new species is morphologically close to P. kranjiensis Johnson, 1970 and P. cinctipes (Randall, 1840), but can be distinguished from those by differences in shape and colour of the carapace, proportions of cheliped articles and cheliped spinulation. Petrolisthes tanmayi sp. nov. differs from all other Indian species of Petrolisthes in the absence of spines in the anterior margin of P1 carpus. Phylogenetic analysis based on mitochondrial COI sequences suggests that P. tanmayi sp. nov. is closely related to P. ornatus Paulson, 1875 and P. armatus (Gibbes, 1850).